EFFORTS TO INCREASE EMPLOYEE JOB SATISFACTION IN THE HOSPITALITY BUSINESS - MAUREN HADISAPUTRA; IAN NURPATRIA SURYAWAN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
Employees are one component of human resources that is important to note because employees have an important role in supporting the success of the company. The purpose of this study was to examine the effect of employee job satisfaction on leadership, team work, and work motivation on XYZ Hotel employees. The method used in this research is descriptive and causality. Data collection was carried out by distributing questionnaires. The sample in this study were 67 employees. The sampling technique in this study used a nonprobability sampling sample with a purposive sampling method. The data analysis technique used in this research is multiple linear regression analysis technique. The methods for analyzing data in this study are normality, classical assumptions, model testing and hypotheses. The result of this study is that leadership and work motivation have a positive effect on employee job satisfaction. While the work team has no effect on employee job satisfaction.